Systematic Literature Review: Trends and Effectiveness of Technology-Based Learning Media in Biology Education - Jatijagad, Shifaq Jahar; Setyono, Prabang; Karyanto, Puguh (Universitas Muhammadiyah Surakarta, 2025)
Technological Advancements Have Significantly Transformed Biology Education, Particularly Through The Use Of Technology-Based Learning Media. This Study Aims To Identify Trends In The Application And Assess The Effectiveness Of Technology-Based Learning Tools In Enhancing Student Learning Outcomes In Biology. Employing A Systematic Literature Review Approach, The Article Analyzes Ten Selected Studies Published Between 2014-2024 And Indexed In International Databases. The Synthesis Of Results Indicates That Interactive Simulations, Augmented Reality (Ar), Virtual Reality (Vr), Mobile Applications, And Interactive Multimedia Significantly Improve Students' Conceptual Understanding, Motivation, And Participation. Most Studies Reported Notable Increases In Post-Test Scores And Active Student Engagement. However, Challenges Such As Limited Infrastructure And Insufficient Teacher Training Remain Barriers To Optimal Implementation. These Findings Confirm That Technology-Based Learning Media Hold Great Potential To Create More Engaging And Meaningful Educational Experiences, Paving The Way For Future Improvements In The Quality Of Biology Education.